2006
DOI: 10.1016/j.jmaa.2005.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Homoclinic orbits for second order self-adjoint difference equations

Abstract: In this paper we discuss how to use variational methods to study the existence of nontrivial homoclinic orbits of the following nonlinear difference equationswithout any periodicity assumptions on p(t), q(t) and f , providing that f (t, x) grows superlinearly both at origin and at infinity or is an odd function with respect to x ∈ R, and satisfies some additional assumptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 17 publications
1
62
0
1
Order By: Relevance
“…So homoclinic orbits have been extensively studied since the time of Poincaré, see [7,8,17] and the references therein. Recently, Ma and Guo [14,15] have found that the trajectories which are asymptotic to a constant state as the time variable |k| → ∞ also exists in discrete dynamical systems [2-6, 11-15, 20-24, 26]. These trajectories are also called homoclinic orbits (or homoclinic solutions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So homoclinic orbits have been extensively studied since the time of Poincaré, see [7,8,17] and the references therein. Recently, Ma and Guo [14,15] have found that the trajectories which are asymptotic to a constant state as the time variable |k| → ∞ also exists in discrete dynamical systems [2-6, 11-15, 20-24, 26]. These trajectories are also called homoclinic orbits (or homoclinic solutions).…”
Section: Introductionmentioning
confidence: 99%
“…In many studies (see, e.g., [3,4,9,11,12,14,15,23]) of second order difference equations, the following classical Ambrosetti-Rabinowitz condition is assumed (AR) there exists a constant β > 2 such that 0 < βF(k, u) uf(k, u) for all k ∈ Z and u ∈ R \ {0}.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study of homoclinic orbits [10][11][12][13][14][15][16][17][18][19][20][21] of difference equation is meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…By using the critical point theory, Guo and Yu [23] established sufficient conditions on the existence of periodic solutions of second-order nonlinear difference equations. Compared to first-order or second-order difference equations, the study of higher-order equations has received considerably less attention (see, for example, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and the references contained therein). Peil and Peterson [26] in 1994 studied the asymptotic behavior of solutions of 2nth-order difference equation…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation